2005
DOI: 10.1016/j.ejcts.2005.08.017
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the pathophysiology of flail segment: the implications of anterior serratus muscle in parietal failure

Abstract: The anterolateral and posterolateral flail segments are rendered susceptible to secondary dislocation through a complex set of factors, of which the action of anterior serratus muscle is obvious. Restoration of parietal mechanics by early surgical reduction/fixation is a reliable therapeutic option in selected patients and offers encouraging results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 20 publications
1
21
0
1
Order By: Relevance
“…The days on a ventilator, ICU LOS, total LOS and rate of pneumonia for operative patients in our study are very similar to previously published results, while our control patients had substantially better outcomes than those published previously. 6,[8][9][10][11][12][14][15][16][17][18][19][20] This supports the notion that surgical fixation of flail chest is not required for all patients.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…The days on a ventilator, ICU LOS, total LOS and rate of pneumonia for operative patients in our study are very similar to previously published results, while our control patients had substantially better outcomes than those published previously. 6,[8][9][10][11][12][14][15][16][17][18][19][20] This supports the notion that surgical fixation of flail chest is not required for all patients.…”
Section: Resultsmentioning
confidence: 54%
“…What is more astounding, however, is how our outcomes compare with previously published outcomes in nonoperative patients. 6,[8][9][10][11][12][14][15][16][17][18][19][20] When compared with the RCT by Marasco and colleagues, days on a ventilator in our study were less than half of theirs, ICU LOS in our study was more than 11 days shorter, and hospital LOS was 9 days shorter, while their pneumonia rates were 3 times higher than ours. 10 Despite our retrospective matched cohort design, our study raises some interesting questions for future examination, especially considering that the only other North American study on this topic also found no significant improvements in LOS or ventilator days with flail chest fixation.…”
Section: Discussionmentioning
confidence: 78%
“…Ahmed and Mohyudin [5] documented that patients with internal fixation of their flail chest remained an average of 3.9 days on mechanical ventilation compared to 15 days for patients managed without internal fixation; and Voggenreiter et al [19] reported significantly shorter periods of mechanical ventilation in patients with operative chest-wall stabilisation. On the other hand, Borrelly et al [20], by studying the pathophysiology of flail segment, suggested restoration of parietal mechanics by early surgical fixation since the anterolateral and postero-lateral flail segments are rendered susceptible to secondary dislocation through a complex set of factors. Unfortunately, all the above-mentioned studies were either retrospective or used groups that were not well matched in terms of the extent of chest-wall injury and overall ISS.…”
Section: Extrathoracic Injuriesmentioning
confidence: 99%
“…Введение травматическая деформация грудной клетки является одним из звеньев патогене-за тяжелой дыхательной недостаточности у пострадавших с множественными перелома-ми ребер [1,2,3]. смещение реберных от-ломков, травматизация подлежащего легко-го и поверхностных мягких тканей, наличие тканевой эмфиземы, уменьшение объема ге-миторакса формируют клинически значимую деформацию грудной клетки, проявляющую-ся болевым синдромом, различными респи-раторными нарушениями, изменениями био-механики каркаса грудной клетки, космети-ческими дефектами [4,5].…”
Section: Abstract: Rib Fracture Traumatic Chest Deformity Fixationunclassified